Self-dual super-Yang-Mills as a string theory in (x, θ) space - Berkovits, Nathan [UNESP] (Springer Nature, 2004)
Different string theories in twistor space have recently been proposed for describing N = 4 super-Yang-Mills. In this paper, a string theory in (x, θ) space is constructed for self-dual N = 4 super-Yang-Mills. It is hoped that these results will be useful for understanding the twistor-string proposals and their possible relation with the pure spinor formalism of the D = 10 superstring. © SISSA/ISAS 2004.
Keywords: Extended Supersymmetry; Superstrings and Heterotic Strings